KONSEP INOVASI KURIKULUM DAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Hafizon, Ahmad; Mansur, Amril; Bakar, Abu (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
This paper contains an explanation the meaning of innovation curriculum and the learning of Islamic religious education. The curriculum is one of the most decisive components in achieving educational goals and also as the guidence in implementing the teaching at all types and levels of education. In Islam, the concept of curriculum means Manhaj, which is a clear way for educators and students to take to develop their knowledge, skills and attitudes. Islamic education curriculum is Islamic education material in the form of activities, knowledge and experiences that are intentionally and systematically given to students in order to achieve the goals of Islamic education.